Normalisation of AHI Under Positive Pressure Therapy Does Not Necessarily Mean Control of Symptoms: A Comparison of the Effectiveness of APAP and CPAP on Daytime Sleepiness and Nocturnal Urination - Sorin Bivolaru; Ancuța Constantin (Life, 2025)
In practice, many patients receive APAP treatment for the simple reason that it provides increased comfort and is easier for patients to accept and tolerate. Reality has proven that we have very many patients diagnosed with OSAS on APAP treatment, under which AHI has normalized, but patients continue to have remaining symptoms. Thus the question was born: is the persistence of remnant symptomatology under APAP related to the mode of ventilation in patients with normalized AHI? The target group was young obese men presenting to the urology service for nocturnal pollakiuria without urologic cause. After performing nocturnal ventilatory polygraphy, the patients were recommended APAP treatment for three months, subsequently, the patients were switched to CPAP treatment for another three months, thus comparing the results obtained. After 6 months of treatment, 71.4% of the subjects would opt to continue CPAP treatment. While a clear option for APAP treatment was expressed by 10.2%. Our research, suggests that we should not be misled by the normalization of AHI under APAP therapy, but to evaluate the patients also with the help of available and standardized questionnaires.